Hatcheries to High Seas: Climate Change Connections to Salmon Marine Survival - Shuichi Kitada; Katherine W. Myers; Hirohisa Kishino (Ecology and Evolution, 2025)
ABSTRACT We investigated variations in the marine survival of Japanese hatchery chum salmon (Oncorhynchus keta) during 25 years of climate change (1998–2023). Japan is the world's largest producer of hatchery salmon and is located near the global southern distribution limit of chum salmon. Our goal was to identify local‐ and context‐specific metrics related to the observed coastwide decline in salmon marine survival over the past 2 decades. We hypothesized multiple metrics in three categories of stressors: hatchery carryovers, ocean conditions, and predators and competitors. The hatchery carryovers are stressors related to hatchery rearing that affect survival at a different life stage. We collected, processed, and collated large publicly available datasets into a comprehensive open‐access database encompassing the life cycle of Japanese chum salmon, from eggs to adult spawners. Multivariate regression models showed that associations between stressors and adult salmon return rate (marine survival) varied by coastal management region, salmon life stage, and seasonal high‐seas distribution area. In the early marine life‐history stage, parental egg size, and fry size‐at‐release had the largest positive model effects on marine survival. The sea surface temperature (SST) at the time of fry release and a predator of fry had significant negative effects. In the offshore and high‐seas life stages, summer SST had negative effects, while winter SST had positive effects. Russian chum and/or pink salmon abundance had negative effects, while no effect was found for North American pink and chum salmon abundance. Generalized additive models (GAMs) identified a nationwide decline in egg size and fry size‐at‐release. Our study highlights the need for an experimental approach to hatchery practices, including monitoring and analyses with updated information, leading to effective management decisions and policies for future sustainability and conservation of salmon resources.